2021
DOI: 10.1186/s13643-021-01586-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of pharmacy in the management of cardiometabolic risk, metabolic syndrome and related diseases in severe mental illness: a mixed-methods systematic literature review

Abstract: Background Individuals with severe mental illness, e.g. schizophrenia have up to a 20% shortened life expectancy compared to the general population. Cardiovascular disease, due to cardiometabolic risk and metabolic syndrome, accounts for most of this excess mortality. A scoping search revealed that there has not been a review of published studies on the role of pharmacy in relation to cardiometabolic risk, metabolic syndrome and related diseases (e.g. type 2 diabetes) in individuals with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…The TG/HDL-C ratio is an atherogenic index that has been proven to be a highly significant independent predictor of myocardial infarction [11]. Patients with schizophrenia are more likely than the general population to develop CVD due to insulin resistance, so lowering the index of insulin resistance with probiotics may contribute to prolong their lives [12]. However, the underlying mechanism by which the probiotic mixture improves constipation and metabolic abnormalities in schizophrenic patients is not fully understood because our study did not include genetic testing of the gut microbiota.…”
Section: Probiotics Improved Both Constipation and Insulin Resistance In Schizophrenic Patientsmentioning
confidence: 99%
“…The TG/HDL-C ratio is an atherogenic index that has been proven to be a highly significant independent predictor of myocardial infarction [11]. Patients with schizophrenia are more likely than the general population to develop CVD due to insulin resistance, so lowering the index of insulin resistance with probiotics may contribute to prolong their lives [12]. However, the underlying mechanism by which the probiotic mixture improves constipation and metabolic abnormalities in schizophrenic patients is not fully understood because our study did not include genetic testing of the gut microbiota.…”
Section: Probiotics Improved Both Constipation and Insulin Resistance In Schizophrenic Patientsmentioning
confidence: 99%
“…Semi‐structured telephone interviews 26 were conducted by the lead researcher, a senior mental health pharmacist (D. S). The topic guide was informed by a literature review, 27 clinical background and experience of the lead researcher and pilot interviews with a patient and an informal carer. The literature review identified a lack of qualitative research exploring the dyadic view of CMR, MetS and related diseases and SMI.…”
Section: Methodsmentioning
confidence: 99%
“…A key aspect of medication optimisation is how prescribing decisions are made—what works and what does not work. Collaborative approaches, such as shared-decision making, involving key practitioner groups (pharmacy, medicine and nursing) working with people living with SMI and family carers hold promise for addressing non-adherence and overprescribing practices 1 8–10 12 13. The potentially coercive nature of treatment for mental health conditions can damage mutual trust between practitioners and people living with SMI, making collaborative approaches more challenging and increasing the risk of medication-related adverse events 14 15.…”
Section: Introductionmentioning
confidence: 99%